PENCIPTAAN SUASANA PENDIDIKAN HOLISTIK, KOMPRENHENSIF, RELIGIUS, DAN RAHMATAN LIL’ALAMIN DI SEKOLAH - Rahmathul Dilfa; Wahyuni Safitri; Regina Okta Audini; Chintia Essa Bella; Ainil Mardiah; Sinta; Hendrizal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to explore the creation of a holistic, comprehensive, religious and rahmatan lil'alamin educational atmosphere in schools. The issue raised was the lack of integration of spiritual and moral values in an education system that often focuses on academic aspects alone. The methodology used was a literature study, which involved analyzing various literatures related to holistic and religious education. The results showed that the religious environment in schools plays an important role in shaping students' character, increasing tolerance and strengthening moral values. In addition, the history of comprehensive holistic education in Indonesia shows that this approach has been recognized as a solution to create a generation that is not only academically intelligent, but also has integrity and social care. This research also found that the foundation of comprehensive holistic education is rooted in rich cultural and religious values, which can be integrated in the curriculum.